THE ANALYSIS OF CAUSAL FACTOR ON STUDENT SPEAKING ANXIETY - Dedy Subandowo (Universitas Ahmad Dahlan)
This article examines the analysis of causal factor on student speaking anxiety. This study is to explain what factors affecting the students speaking anxiety. Moreover, the research data are taken from the second semester students of English Education Study Program, Muhammadiyah University of Metro. This is a descriptive qualitative study and some instruments such as documentation, interview, observation are used in order to collect the data. The data is then analyzed by some steps, like data collection in which writer gathers all of the data that will be used to complete the research. After collecting the data, the writer sorts the data by summarizing and choosing the specific category, displaying the data, verifying the data analysis, and making a conclusion from the finding data. The result of this research shows the students speaking anxiety causal factors in the second semester. Most of the students feel anxious when speaking English in the class. Eventually, some suggestions are discussed in order to help students reduce anxiety and become more confident to speak English in oral language classrooms.